Oxidation of styrene over molybdenum-containing hydrotalcite catalysts - Thao, Nguyen Tien; Long, Dang Van (Vietnam Journal of Chemistry, 2016)
Mg0.6Al0.4(OH)2(MoO4)0.2.mH2O was prepared via coprecipitation method and characterized by XRD, BET, EDS techniques. The solid has a hydrotalcite-like structure and molybdate anions stayed in the interlayer regions between two brucite sheets. The synthesized material has been used as heterogeneous catalyst for the liquid oxidation of styrene with air. The oxidation reaction was carried out at atmospheric pressure in the temperature range of 60-110 oC. The presence of molybdate anions plays role of active site for the conversion of styrene into benzaldehyde and styrene epoxide with the selectivity of 97-99 %. Keywords. Benzaldehyde, epoxide, molybdate, LDH, intercalation.